2008
DOI: 10.2134/jeq2007.0468
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration into Cropped Soils: Effect of Rain and Sodium Adsorption Ratio–Impacted Irrigation Water

Abstract: Th e sodium adsorption ratio (SAR) and salinity criteria for water suitability for irrigation have been developed for conditions where irrigation water is the only water source. It is not clear that these criteria are applicable to environments where there is a combination of rain and irrigation during the growing season. Th e interaction of rainfall with irrigation water is expected to result in increased sodicity hazard because of the low electrical conductivity of rain. In this study we examined the eff ect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…SAR is a measure of the sodicity of soil, as determined from analysis of water extracted from the soil. The formula for calculating SAR is (Suarez et al, 2008):…”
Section: Introductionmentioning
confidence: 99%
“…SAR is a measure of the sodicity of soil, as determined from analysis of water extracted from the soil. The formula for calculating SAR is (Suarez et al, 2008):…”
Section: Introductionmentioning
confidence: 99%
“…Electrokinetic phenomena and effects on pore structure and flow Suarez et al (2008) investigated the reduction of infiltration rate into cropped soils and concluded that an increase in the sodium adsorption ratio (SAR) caused changes in pore structure, eventually reducing the infiltration capacity. The SAR is calculated as follows:…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Adsorption of sodium and release of calcium and magnesium (due to salt application) resulted in a substantial increase of the sodium adsorption ratio. Suarez et al (2008) suggested that an FIG. 5.…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the infiltration qualities of the soil, sodium adsorption ratio (SAR) and electrical conductivity (EC) data were analyzed. Typically, EC to SAR ratio is a good indicator of the infiltration capacity of the soil (Suarez et al 2008); http://waterquality.montana.edu/docs/methane/ basics_highlight.shtml, accessed 26 July 2009). Figure 9 shows the relationship between salinity as EC, sodicity as SAR, and infiltration rates.…”
Section: Groundwater Vulnerabilitymentioning
confidence: 99%